HyNote: Integrated Concept Mapping and Notetaking - Meng, Xiaojun; Zhao, Shengdong; Edge, Darren (International Working Conference on Advanced Visual Interfaces (AVI '16), 2016)
Notes can be taken in a linear or nonlinear way. Previous work suggests that nonlinear note taking is advantageous in terms of sense-making and long-term recall. However, previous studies also reveal that the combination of divided attention and time pressure make realtime notetaking a challenge. In this paper, we propose a new hybrid workflow inheriting advantages from both linear and nonlinear notetaking approaches. Our resulting HyNote (Hybrid Notetaking) system uses statistical parsing of linear raw notes to facilitate concepts mapping, allowing users to smoothly switch between linear and nonlinear approaches with low effort and time costs. Results from our preliminary study of HyNote show that users can easily map concepts in realtime and achieve superior understanding of lecture contents in a video learning task compared with using the traditional linear Notepad application.